Prevalence of Head Injury of Patients Arriving in a Tertiary Care Center - Yadav, Arbindra Kumar; Rajbanshi, Jagat Narayan; Kushwaha, Saroj Kumar; Nepal, Pankaj Raj (Eastern Green Neurosurgery, 2020)
Background and purpose: The prevalence of head injury is increasing with increasing number of automobiles, especially motorbike. With the objective to evaluate the prevalence of head injury and factors that could affect the severity of head injury, this study was performed in a tertiary hospital at far- eastern Nepal.Methodology: This is a cross-sectional study over the duration of one year. Association of age, gender, and mode of injury was checked with severity of injury using Chi-square test where P-value was kept significant at